The anatomy of myth : the art of interpretation from the presocratics to the church fathers - Herren, Michael W. (Oxford University Press, 2017)
'The Anatomy of Myth' is a comprehensive study of the methods of interpreting authoritative myths from the Presocratic philosophers to the Neoplatonists and their adoption by the Church Fathers